Microwave-induced spin-flip scattering of electrons in point contacts - Kadigrobov, A.M.; Shekhter, R.I.; Aronov, I.; Kulinich, S.I.; Pulkin, A.; Jonson, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
We investigate resonant interaction of conduction electrons with an electromagnetic field that irradiates apoint contact between a ferromagnetic and a normal metal in the presence of a strong magnetic field of order 1 T.We show that electron spin-flips caused by resonant absorption and stimulated emission of photons result in asharp peak in the magnetic-field dependence of the point-contact resistance. The height of the peak is shown tobe directly proportional to the net rate of energy transfer to the electromagnetic field in the point contact due toabsorption and stimulated emission of photons. Estimations indicate that our theory can serve as a basis for theexplanation of recent experiments [A.M. Kadigrobov et al., New J. Phys. 13, 023007 (2011)].